2017
DOI: 10.1016/j.cmi.2017.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic and symptomatic urethral gonorrhoea in men who have sex with men attending a sexual health service

Abstract: The findings from our study lend support to guidelines that recommend screening asymptomatic MSM for urethral gonorrhoea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 17 publications
6
23
0
Order By: Relevance
“…Also, we only tested men for urethral gonorrhoea if they were symptomatic and hence we may have missed asymptomatic urethral infections. However, previous studies have shown that asymptomatic urethral gonorrhoea is rare, [ 23 , 36 ] hence the omission of asymptomatic urethral screening should not have significantly affected our results. Thirdly, we used culture tests rather than NAAT for detection of gonococci.…”
Section: Discussionmentioning
confidence: 75%
“…Also, we only tested men for urethral gonorrhoea if they were symptomatic and hence we may have missed asymptomatic urethral infections. However, previous studies have shown that asymptomatic urethral gonorrhoea is rare, [ 23 , 36 ] hence the omission of asymptomatic urethral screening should not have significantly affected our results. Thirdly, we used culture tests rather than NAAT for detection of gonococci.…”
Section: Discussionmentioning
confidence: 75%
“…Fourth, due to the low rates of testing for gonorrhoea in heterosexual males over the study period, we have had to calculate positivity by using the number of men tested for chlamydia. However, because gonorrhoea is almost always symptomatic in men, 22 this should be a reasonably accurate method for calculating positivity because it is unlikely that those not tested for gonorrhoea would be positive, and this method has been previously used in other studies. 3,11 Thus, our findings may also be biased towards symptomatic males because they are more likely to present at the clinic and test positive.…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of asymptomatic NG and CT has been widely reported, but results vary widely around the world, ranging from 8% to 87%. [14][15][16][17] The disparities in the proportion of asymptomatic participants with or without STIs may be attributed to the different laboratory methods employed, the distribution of risk factors and the composition of the population studied. Given that one-third of CT infections are asymptomatic, passive screening in Shenzhen (i.e., screening patients for medical treatment) is not enough.…”
Section: Plos Onementioning
confidence: 99%